Treatments and outcomes of neonatal disseminated intravascular coagulation with and without neonatal asphyxia: A retrospective study using nationwide data in Japan - Hiroki Kitaoka; Takaaki Konishi; Yoshihiko Shitara; Atsushi Ito; Kohei Kashima; Yohei Hashimoto; Hiroki Matsui; Motohiro Kato; Naoto Takahashi; Hideo Yasunaga (Pediatrics and Neonatology, 2024)
Background: Although neonatal disseminated intravascular coagulation (DIC) is associated with high mortality and severe complications, few studies have reported its clinical course. We aimed to describe the characteristics, treatments, and outcomes of neonatal DIC by using a national inpatient database. Methods: Using the Japanese Diagnosis Procedure Combination database, we identified 5533 patients with neonatal DIC who were admitted to neonatal intensive care units between July 2010 and March 2020. We categorized the patients into those with asphyxia (n = 2911) and those without asphyxia (n = 2622). We investigated the patient characteristics, treatments, and outcomes. We further categorized neonates with asphyxia according to its severity. Results: The gestational age of neonates with asphyxia was significantly lower than that of neonates without asphyxia (P < 0.001). Antithrombin was most commonly used for DIC (40%). Neonates with asphyxia were more likely to receive antithrombin (43% vs. 38%; P < 0.001), recombinant human soluble thrombomodulin (28% vs. 20%; P < 0.001), and fresh frozen plasma transfusion (68% vs. 51%; P < 0.001) than those without asphyxia. Neonates with asphyxia had higher in-hospital mortality (17% vs. 10%; P < 0.001), severe bleeding (11% vs. 6.8%; P < 0.001), and hospitalization costs than those without asphyxia. Additionally, neonates with severe asphyxia were more likely to receive several DIC therapies (such as recombinant human soluble thrombomodulin [30% vs. 24%]) and had higher in-hospital mortality (19% vs. 11%) and hospitalization costs than those with mild asphyxia. Conclusions: In this large retrospective study of neonatal DIC, patients with asphyxia received several treatments and demonstrated unfavorable outcomes when compared to those without asphyxia.